Judicial Review of Government Regulation Number 24 of 2016 Concerning Amendment to Government Regulation Number 37 1998 Concerning Land Deed Official Position Regulations - Supardin; Febriani, Zelis; Ilwan, M.; Kaharudin, (International Journal of Scientific Research and Management (IJSRM), 2020)
This research is to find out and understand the legal status of the delegation of government regulations to other government regulations and the juridical consequences of Government Regulation Number 24 of 2016 concerning Amendments to Government Regulation Number 37 of 1998 concerning Land Deed Official Position Regulations that are formed not in accordance with statutory regulations. This research is a normative legal research. Normative legal research is legal research that places law as a norm building system. The norm system in question is about the principles, norms, rules, and regulations. Using the legal approach and conceptual approach. The technique of collecting legal materials using document study techniques is then processed by legal materials and analyzed normatively prescriptive using deductive logic. Based on the results of the study it can be concluded that the legal status of the delegation of authority to form government regulations delegated from other government regulations is invalid, because government regulations are formed to carry out the law as it should, not to carry out the provisions of other government regulations. Juridical consequences of Government Regulation Number 24 of 2016 concerning Amendments to Government Regulation Number 37 of 1998 concerning Land Deed Official Position Regulations that are formed not in accordance with statutory regulations are null and void because they cannot provide legal certainty. This is because the formation of these government regulations is not in accordance with the principles of establishing the rules of law stipulated in Law Number 12 of 2011. The impact of this Government Regulation can be revoked because it does not comply with the principles of the formation of laws and regulations.